2005
DOI: 10.1074/jbc.m408971200
|View full text |Cite
|
Sign up to set email alerts
|

Genes Regulated in Neurons Undergoing Transcription-dependent Apoptosis Belong to Signaling Pathways Rather than the Apoptotic Machinery

Abstract: Neuronal apoptosis has been shown to require de novo RNA/protein synthesis. However, very few genes whose expression is necessary for inducing apoptosis have been identified so far. To systematically identify such genes, we have used genome-scale, long oligonucleotide microarrays and characterized the gene expression profile of cerebellar granule neurons in the early phase of apoptosis elicited by KCl deprivation. We identified 368 significantly differentially expressed genes, including most of the genes previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…The minimum level of Mcl-1 (approximately 40% of the control) was reached 4-6 h after KCl and serum deprivation, depending on the experiments. This coincided with cytochrome c release from mitochondria, 14 dephosphorylation (and thus activation) of GSK3 ( Figure 1a) and caspase 3 activation (Figure 1a). The reduction of the Mcl-1 protein level was associated with a similar decrease in the mcl-1 mRNA level: about 35% reduction between K25 and K5 conditions after 4-8 h of deprivation ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum level of Mcl-1 (approximately 40% of the control) was reached 4-6 h after KCl and serum deprivation, depending on the experiments. This coincided with cytochrome c release from mitochondria, 14 dephosphorylation (and thus activation) of GSK3 ( Figure 1a) and caspase 3 activation (Figure 1a). The reduction of the Mcl-1 protein level was associated with a similar decrease in the mcl-1 mRNA level: about 35% reduction between K25 and K5 conditions after 4-8 h of deprivation ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…We initially identified Trim17 as one of the most highly upregulated genes in CGN following KCl deprivation. 34 To determine whether NFATc3 could be involved in this transcriptional induction, CGNs were transduced with two different shRNAs, which efficiently reduced endogenous NFATc3 expression (Figure 7c, left panel). Importantly, the increase in Trim17 mRNA levels triggered by serum/KCl deprivation was significantly reduced by these two shRNAs (Figure 7c, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…DNA microarray has proved useful for screening cellular targets that govern apoptosis [18,25]. Our most recent studies, in particular, were the first to extend the analysis to survival and led to the identification of key drug targets deregulated in both apoptosis and growth factor rescue [11,15,26].…”
Section: Genomic Approachmentioning
confidence: 99%
“…By using a brain-biased array, this study profiled the gene expression changes of cerebellar granule neurons (CGNs) induced by different apoptotic signals, including potassium and serum withdrawal (KS-W) [21]. Important progress in understanding the apoptotic program elicited by KCl deprivation derived from genome scale studies based on oligonucleotide microarrays, which identified a great number of temporally coupled genes that delineate functional pathways mobilized during neuronal PCD [14,18]. The limitations of the first studies in encompassing the entire set of deregulated genes in neuronal apoptosis were overcome with the advent of whole-genome microarrays, which allowed the whole apoptotic program to be analyzed [19].…”
Section: Genomic Approachmentioning
confidence: 99%
See 1 more Smart Citation